Celiac disease‐associated Neisseria flavescens decreases mitochondrial respiration in CaCo‐2 epithelial cells: Impact of Lactobacillus paracasei CBA L74 on bacterial‐induced cellular imbalance. (20th May 2019) - Labruna, Giuseppe; Nanayakkara, Merlin; Pagliuca, Chiara; Nunziato, Marcella; Iaffaldano, Laura; D'Argenio, Valeria; Colicchio, Roberta; Budelli, Andrea L.; Nigro, Roberto; Salvatore, Paola; Barone, Maria Vittoria; Sacchetti, Lucia
Abstract: We previously identified a Neisseria flavescens strain in the duodenum of celiac disease (CD) patients that induced immune inflammation in ex vivo duodenal mucosal explants and in CaCo‐2 cells. We also found that vesicular trafficking was delayed after the CD‐immunogenic P31‐43 gliadin peptide‐entered CaCo‐2 cells and that Lactobacillus paracasei CBA L74 ( L . paracasei ‐CBA) supernatant reduced peptide entry. In this study, we evaluated if metabolism and trafficking was altered in CD‐ N . flavescens ‐infected CaCo‐2 cells and if any alteration could be mitigated by pretreating cells with L . paracasei ‐ CBA supernatant, despite the presence of P31‐43. We measured CaCo‐2 bioenergetics by an extracellular flux analyser, N . flavescens and P31‐43 intracellular trafficking by immunofluorescence, cellular stress by TBARS assay, and ATP by bioluminescence. We found that CD‐ N. flavescens colocalised more than control N . flavescens with early endocytic vesicles and more escaped autophagy thereby surviving longer in infected cells. P31‐43 increased colocalisation of N . flavescens with early vesicles. Mitochondrial respiration was lower ( P < .05) in CD‐ N . flavescens ‐ infected cells versus not‐treated CaCo‐2 cells, whereas pretreatment with L . paracasei ‐CBA reduced CD‐ N . flavescens viability and improved cell bioenergetics and trafficking. In conclusion, CD‐ N . flavescens induces metabolic imbalance in CaCo‐2 cells, and the L . paracasei ‐CBA probiotic could be used to correct CD‐associated dysbiosis.